The fibronectin leucine-rich repeat transmembrane protein Flrt2 is required in the epicardium to promote heart morphogenesis. - Müller, P; Schulz, R; Maretto, S; Costello, I; Srinivas, S; Bikoff, E; Robertson, E (2011)
The epicardium, the outermost tissue layer that envelops the developing heart and provides essential trophic signals for the myocardium, derives from the pro-epicardial organ (PEO). Two of the three members of the Flrt family of transmembrane glycoproteins, Flrt2 and Flrt3, are strongly co-expressed in the PEO. However, beginning at around day 10 of mouse development, following attachment and outgrowth, Flrt3 is selectively downregulated, and only Flrt2 is exclusively expressed in the fully delaminated epicardium. The present gene-targeting experiments demonstrate that mouse embryos lacking Flrt2 expression arrest at mid-gestation owing to cardiac insufficiency. The defects in integrity of the epicardial sheet and disturbed organization of the underlying basement membrane closely resemble those described in Flrt3-deficient embryos that fail to maintain cell-cell contacts in the anterior visceral endoderm (AVE) signalling centre that normally establishes the A-P axis. Using in vitro and in vivo reconstitution assays, we demonstrate that Flrt2 and Flrt3 are functionally interchangeable. When acting alone, either of these proteins is sufficient to rescue functional activities in the AVE and the developing epicardium.